(untitled) (Research, Society and Development, 2021)
The contribution of Information and Communication Technologies (ICTs) to the improvement of daily living skills of students with intellectual disability is a topic that has been of great concern to scientists in recent years. In the present systematic review, there has been an attempt to explore the potential of new technologies for the education, the improvement of the adaptive skills and the academic and social inclusion of students with intellectual disability, since they comprise a large part of the population with special educational needs. The review includes research of the last seventeen years on daily living skills, literacy, learning geometric concepts and shapes, focused attention, gross and fine motor skills, and visual-motor coordination. We consider that learning is facilitated with the use of ICTs, as students with intellectual disability are enabled to have equal access to innovative programs, curricula and classroom participation. Moreover, the training and education programs provided through ICTs seem to have a substantial and permanent impact on the quality of their lives, finally aiming at their social and vocational inclusion.